LIGHT SPATIAL AND BAR CONSTRUCTION OF COVERS - Tamazy Leonidovich Kobaliya; Pavel Sergeevich Chernov; Alexander Surenovich Marutyan (Современная наука и инновации, 2022)
The author describes double-deck cantilever and large-span modifications of spatial constructions of covers consisting of bar and nodal elements of Kislovodsk (MArhI) type modules.